Predictors of Satisfaction in Men After Penile Implant Surgery. Issue 8 (15th July 2018) - Habous, Mohamad; Tal, Raanan; Tealab, Alaa; Aziz, Mohammed; Sherif, Hammoda; Mahmoud, Saad; Abdelwahab, Osama; Nassar, Mohammed; Kamil, Usama; Abdelrahman, Ziad; Binsaleh, Saleh; Giona, Simone; et al.
Abstract: Introduction: Despite the high satisfaction with penile implant (PI) surgery reported in the literature, a significant proportion of patients remain dissatisfied. Aim: To evaluate satisfaction after PI surgery, using a single question and a scoring system. Furthermore, we attempted to define factors that predicted high patient satisfaction. Methods: The study population consisted of all patients undergoing PI surgery between 2009 and 2015. Comorbidity, demographic, and implant information were recorded. Complications recorded included: minor (requiring no re-operation) such as penile or scrotal hematoma, superficial wound breakdown; major (requiring hospitalization or re-operation) such as device infection, erosion, and mechanical malfunction. Patient satisfaction was defined using a single question posed to the patient 6 months after surgery using a 5-point Likert scale (5 being the most satisfied). Descriptive statistics were used to define complication rates and multivariable analysis (MVA) was performed to define predictors of high satisfaction (score ≥ 4), including presence and degree of complications, Peyronie's disease (PD), diabetes mellitus (DM), number of vascular comorbidities, body mass index (BMI) > 30, and patient age. Main Outcome Measure: Patients with a major complication, with or without an additional minor complication, had a higher likelihood of being dissatisfied (25%) compared to patients with no complication or only minor complication 1.9% (no complications) and 3.7% (only minor complications), P < .001. Results: 902 patients were analysed. Mean age was 56.6 ± 10.6 years. Mean BMI was 30 ± 5. Comorbidity profile was diabetes 75%, dyslipidaemia 44%, hypertension 33%, cigarette smoking 32%, and PD 34%. 76% had a malleable implant (MPP) and 24% an inflatable implant (IPP). 31% had a minor complication and 9% a major complication. 93% had high satisfaction (score ≥4). Patients with any complication had a reduced rate of high satisfaction (97.5% vs 87.7%; P < .001) and even more pronounced with a major complication (96.7% vs 64.2%; P < .001). On MVA, only the absence of a major complication was a significant predictor of high satisfaction (OR 20, 95% CI 9-50, P < .001). Conclusion: A high percentage of men are satisfied after penile implant surgery. Only the presence of a major complication is linked to a lower likelihood of achieving high satisfaction.